2017
DOI: 10.1111/bjh.14625
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of the impact of treatments and blood counts on survival and the risk of vascular events during the course of polycythaemia vera

Abstract: Vascular and non-vascular complications are common in patients with polycythaemia vera. This retrospective study of 217 patients with polycythaemia vera aimed to determine whether blood counts with respect to different treatments influenced the complication rate and survival. We found that 78 (36%) patients suffered from at least one complication during follow-up. Older age and elevated lactate dehydrogenase at diagnosis were found to be risk factors for vascular complications. When the vascular complication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In a retrospective study of PV to determine whether blood counts influenced the complication rate and survival, older age and elevated LDH level at diagnosis were found to be risk factors for vascular complications. When the vascular complication occurred, 41% of the patients with a complication had elevated WBC counts compared with 20% of patients without a complication (Enblom‐Larsson et al , ).The CYTO‐PV study treatment arms, which showed a lower thrombotic risk in those intensively managed to Hct <0·45, showed a comparatively lower WBC count, which may have contributed to the lower rate of thrombotic events (Marchioli et al , ) (McMullin et al , ). There is no evidence from randomised trials to determine whether treatment targeted at reducing leucocyte count impacts on overall outcome and therefore no recommendation to target WBC counts as a treatment goal can be made.…”
Section: Platelet and Leucocyte Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of PV to determine whether blood counts influenced the complication rate and survival, older age and elevated LDH level at diagnosis were found to be risk factors for vascular complications. When the vascular complication occurred, 41% of the patients with a complication had elevated WBC counts compared with 20% of patients without a complication (Enblom‐Larsson et al , ).The CYTO‐PV study treatment arms, which showed a lower thrombotic risk in those intensively managed to Hct <0·45, showed a comparatively lower WBC count, which may have contributed to the lower rate of thrombotic events (Marchioli et al , ) (McMullin et al , ). There is no evidence from randomised trials to determine whether treatment targeted at reducing leucocyte count impacts on overall outcome and therefore no recommendation to target WBC counts as a treatment goal can be made.…”
Section: Platelet and Leucocyte Targetmentioning
confidence: 99%
“…The efficacy of HC in controlling blood counts and preventing thrombosis has been extrapolated from the evidence in ET (Cortelazzo et al , ) and HC has been used in the management of PV. A recent retrospective study of PV demonstrated that patients treated with HC experienced significantly fewer vascular complications (11%) than patients treated with venesection only, with a survival advantage for patients treated with HC when adjusted for variables supporting the use of this agent in first‐line treatment (Enblom‐Larsson et al , ).…”
Section: Cytoreductive Therapymentioning
confidence: 99%
“…Treatment focuses on prevention of these complications. It has been reported that patients treated with hydroxyurea had fewer vascular events as compared with those treated by phlebotomy alone [ 20 ]. Barbui et al [ 21 ] compared hydroxyurea therapy with phlebotomy in PV patients and reported fewer cardiovascular events and hematological transformations (myelofibrosis transformation and acute leukemic transformation) as well as decreased overall mortality in those using hydroxyurea.…”
Section: Discussionmentioning
confidence: 99%
“…The greater added benefit of cytoreductive drugs over phlebotomy in PV is based on the results of the Polycythemia Vera Study Group 01-PVSG study, 16 a propensity score analysis of the European Collaboration on Low-dose Aspirin in Polycythemia Vera (ECLAP) 17 prospective study and one recent retrospective cohort analysis. 18 Nonetheless, experts discourage the use of cytoreductive drugs in clinical practice for young patients without previous thrombosis since the supposed leukemogenic risk associated with the currently available drugs, such as hydroxyurea, although largely uncertain, might outweigh the possible antithrombotic benefits.…”
Section: Should Cytoreduction Be Prescribed To All Patients With Polymentioning
confidence: 99%